Práticas educativas culturais e escolarização na capitania de Mato Grosso (1748-1822) - Dourado, Nileide Souza (2014)
Highlight the various forms of education do - school and non-systematic nature - was the object of this thesis. For this, it employed the categories " educate " and "train " , important aids in the understanding of learning achieved in the space of educational practices streamlined by colonizers and colonized and revealed in the social spaces of the captaincy of Mato Grosso , particularly in the Village real Good Jesus of the Cuiabá and Vila Bela the Holy Trinity. The inclusion of a broader look at the educational landscape in this region and the hinterland border, in years seven and eight was only possible by the appropriation of a rare set of documents, carries rich information on data on cultural and educational practices of schooling in captaincy of Mato Grosso. In the field of formal education , emphasis was given to the reforms , either by the institution of royal classes in Cuiaba and Vila Bela , the procedures used to fill the seats , the hiring and activities of royal teachers , substitutes and individuals, in schools , and reforms also displacement of Mato Grosso students for higher studies in Portugal, among other aspects . To that extent, the institutions - the municipalities, the Church, the Military and the Men of Science - were fundamental to understand the role of these agents in the colonial setting and its close relationship with educating and instructing. The study also drew attention to the non-school dimension, manifested by the circularity of knowledge necessary for the development of technical activities of military engineering and teaching crafts, essential in building and ensuring security in oestina border. Michel de Certeau , Roger Chartier, Norbert Elias , Carlo Ginsburg, Comenius, Sergio Buarque Holanda commodification and offered loupes with which it was possible to see the places of educational practices and education of the residents of the Village of Cuiabá and Vila Bela. With them, it was possible to work in the field of cultural history, with the categories of education and instruction produced in the context of the Enlightenment, and that supported the reforms of Pombal Education. In this construction, then empiricism traditionally used by historiography was supplemented with unpublished documents have been analyzed in close dialogue with contemporary historiographical production that comes from the Brazilian Mato Grosso and territory in the first half and seven of eight . For this, it was necessary to extend the approaches with the backdrop of the relations of sociability present within the territory of Mato Grosso; they have been manifest in the school or non-school dimension.